Studies on the Dielectric Constant, AC Electrical Conductivity and AC Electrical Modulus of V2O5 Addition Lithium-Zinc Ferrites - Islam, S M Rubayatul; Shikder, M Rasel; Ullah, M Samir (Bangladesh Journal of Physics, 2023)
This study investigates the electrical transport features of V2O5 added Li-Zn ferrites. The ferrites have the compositions Li0.25Zn0.50Fe2.25O4 + xV2O5 (where x = 0.4, 0.8 and 1.2 wt %) and are prepared by the solid-state reaction technique. Frequency-dependent dielectric constant and ac conductivity of the samples have been investigated at room temperature. An enhancement of dielectric constant and ac conductivity is observed with V2O5 addition and displayed a decreasing trend for higher V2O5 addition. The Nyquist impedance plots of the samples display a single semicircular arc, indicating that the conduction mechanism of Li-Zn ferrites occurs through the grain property. Bangladesh Journal of Physics, Vol. 30, Issue 1, pp. 35-41, June 2023